IDENTIFYING ANKLE INJURY PATTERNS OF NETBALL PLAYERS FOR MAINTAIN THEIR HEALTH AND WELLBEING - D.M.D.N Bandara; A.W Suraj Chandana (Gladi : Jurnal Ilmu Keolahragaan, 2021)
Netball is a ball game played by two groups of seven players. Its improvement, got from early forms of ball, started in England during the 1890s. By 1960, universal playing guidelines had been institutionalized for the game. The ankle joint is a pivot joint framed between the tibia and fibula and the bone and enables the foot to twist upwards and downwards. The joint likewise permits a modest quantity of pivot. The joint's dependability originates from the basic course of action of the bones and the encompassing tendons. Ankle injuries can transpire at any age. This article surveys epidemiological investigations on ankle injuries in netball, and what are the sorts of ankle injuries, how it's happen and also survey how counteractive action from ankle injuries and aversion strategies. Furthermore, talk about around a few activities that can use for prevent from ankle injuries in netball. The purpose of the study was to investigate the several Ankle injuries of netball players in different countries. The methodology used for this review was based on previously published guidelines. It included research articles, journals, research publications, reviews and books. Collect all the findings and add the references. Of 47 articles are found and 18 are included in this review essay. Results demonstrate that the ankle injury was the most widely recognized harmed body site in netball and an Ankle sprain was the real lower leg damage happen in Netball. Ankle sprains represent an enormous level of wounds supported in netball. This efficient survey gives a synopsis of the study of disease transmission of ankle damage in Netball.